Day 2 Tue, November 14, 2017 2017
DOI: 10.2118/188479-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Thermally Stable Synthetic Polymer for Harsh Conditions of Middle East Reservoirs. Part I. Thermal Stability and Injection in Carbonate Cores.

Abstract: A great number of Middle East fields have too harsh reservoir conditions (high temperature, high salinity) for conventional EOR polymers used as mobility control agents. Traditional synthetic polymers such as partially hydrolyzed polyacrylamide (HPAM) are not thermally stable. At temperatures above 70°C, acrylamide moieties hydrolyze to acrylate groups which ultimately may lead to precipitation and total loss of viscosifying power. Thermal stability can be improved by incorporating specific mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The polymer is produced by SNF, Andrézieux-Bouthéon, France. The molecular weight of the samples used is about 8 million g/mol, but the product has been produced in a range of molecular weights [ 13 , 14 , 15 ].…”
Section: Simulation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer is produced by SNF, Andrézieux-Bouthéon, France. The molecular weight of the samples used is about 8 million g/mol, but the product has been produced in a range of molecular weights [ 13 , 14 , 15 ].…”
Section: Simulation Approachmentioning
confidence: 99%
“…Most of the proposed screening criteria for polymer flooding applications in the literature suggest a temperature below 100 °C and formation water salinity below 100,000 ppm for a successful implementation [ 11 ]. Recent studies have shown that stability of HPAM could be improved by introducing 2-Acrylamido-2-Methyl Propane Sulfonate (AMPS) as a copolymer [ 13 , 14 , 15 , 16 , 17 , 18 ]. They reported excellent thermal stability and salinity tolerance of SAV10, a high-AMPS-content acrylamide polymer manufactured by SNF, at temperatures between 120 and 140 °C and salinities up to 244,000 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Dupuis et al produced comparable results in their investigations on these polymers [ 169 ]. Furthermore, various rheological investigations of ATBS-based polymer and injectivity on three carbonate rock samples revealed that these polymers need to be salinity tolerant [ 170 ].…”
Section: Experimental Laboratory Studiesmentioning
confidence: 77%
“… Investigations into the capabilities of Superpusher SAV10 (which had significantly more than 35 mol% ATBS and no NVP) and Superpusher SAV333 (which was functionalized with ATBS and 30–45% NVP) in a hard brine (TDS of 84,500 ppm and 6000 ppm hardness) at a temperature of 140 C revealed that SAV10 could retain over 60% of its viscosity after a 6-month period, while SAV333 maintained over 90% of its viscosity. Dupuis et al [ 169 ] made similar discoveries while studying these polymers. …”
Section: Experimental Laboratory Studiesmentioning
confidence: 81%
“…We emphasize that for carbonates in harsh reservoirs the restoration is particularly important since the carbonate rock can become more oil-wet when exposed to increased concentration of divalent cations in the brine. Thus, aging in reservoir oil aims to preserve injectivity and reduce the retention on the rock surface (Dupuis, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%